Aggregate Size Distribution and its Relationship to Physical and Chemical Properties of Some Typical Soils of Kerala - Ushakumary K (Department of Soil Science and Agricultural Chemistry, College of Horticulture, 1983)
The present study was undertaken to evaluate the structural indices of some typical soil groups of Kerala namely, laterite, black, red loam, riverine and coastal alluvium and to relate them to some physico-chemical properties of soils. Soil groups were selected from five extensively occurring series namely, Velappaya, Valiavallampathy, Vellayani, Ponnamattom and Beypore series covering Trichur, Palghat, Trivandrum, Ernakulam and Calicut districts, respectively. Three profiles were chosen from each series and from each profile, samples were collected at four depths viz., 0-15, 15-30, 30-45 and 45-60 cm. The experimental results revealed that the aggregates greater than 0.25 mm were found to be in appreciable amount in all the soils except for few layers in riverine and coastal alluvium. This indicated good structural status of the soils. Black soils have distinctly superior aggregation in comparison to the rest of the soils under investigation. Some of the physico-chemical properties like clay, organic matter, CEC and sesquioxide plays an important role in building soil structure in most of the soil group except riverine alluvium. This is because of the comparatively recent origin of riverine alluvium soils. The texture of the soils varied from clay to loam. The black soils were exclusively clay in texture. Riverine alluvium and coastal alluvium were found to be of clay loam and sandy clay loam in texture, respectively. An increase in finer fraction content with depth was observed. Black soils could retain more water at any given tension and were also superior in available water status. Infiltration rates were high in all soil groups except for black soil and riverine alluvium which were uniformly finer in texture. Except black soils, all other soils were acidic in reaction and have comparatively low CEC. Black soils showed highest value for CEC. Laterite and red soils were richer in sesquioxide content compared to other soil groups. Thus the results clearly indicates that black soils were relatively well aggregated as compared to other soil groups. They were also superior to other soil groups in respect of CEC and available water status, Laterite, red loam and coastal alluvium soils were highly pervious whereas black and riverine alluvium soils relatively less pervious. The former groups of soils were also very poor in respect of their available water status. The rate and stability of aggregation in these soils were more or less of similar type.